Condensation properties of stress granules and processing bodies are compromised in myotonic dystrophy type 1 - Selma Gulyurtlu; Monika S. Magon; Patrick Guest; Panagiotis P. Papavasiliou; Kim D. Morrison; Alan R. Prescott; Judith E. Sleeman (The Company of Biologists, 2022)
RNA regulation in mammalian cells requires complex physical compartmentalisation, using structures thought to be formed by liquid-liquid phase separation. Disruption of these structures is implicated in numerous degenerative diseases. Myotonic dystrophy type 1 (DM1) is a multi-systemic trinucleotide repeat disorder resulting from an expansion of nucleotides CTG (CTGexp) in the DNA encoding DM1 protein kinase (DMPK). The cellular hallmark of DM1 is the formation of nuclear foci that contain expanded DMPK RNA (CUGexp) (with thymine instead of uracil). We report here the deregulation of stress granules (SGs) and processing bodies (P-bodies), two cytoplasmic structures key for mRNA regulation, in cell culture models of DM1. Alterations to the rates of formation and dispersal of SGs suggest an altered ability of cells to respond to stress associated with DM1, while changes to the structure and dynamics of SGs and P-bodies suggest that a widespread alteration to the biophysical properties of cellular structures is a consequence of the presence of CUGexp RNA.